Creation of a data marketplace for monetization of personal data - Bazinovs, Deniss (Riga Graduate School of Law, 2020)
Today, personal data is being actively traded, and in most cases even without the awareness of the data subjects. The regulations such as the General Data Protection Regulation (GDPR) require data controllers and processors to be compliant with many preconditions. And this positively influences the transparency of the data processing, however, there are still many lawful grounds for processing personal data, and often, this still leaves data subjects outside of the monetization of their personal data. And while the ownership of data is still an open discussion, many initiatives and scholarly works have been aimed at restoring the balance and giving the control over data back to the data subjects. This is especially important in the healthcare industry, where research organizations and pharmaceutical companies have grasped everything that was possible from anonymized data and shifted the demand toward personal health data with updating insides from the data subjects themselves and their connected devices, such as smart watches. This requires a different approach, and in author’s opinion a data marketplace for personal data. The author suggests a model of a data marketplace within the territory of European Union (EU). So this work discusses the the current EU legislations, how currently data is being monetized and sold, how many scholars see the potential model of the data marketplace and any other data sharing or trading platform, and the model proposed by the author, and the potential legal issues related to the creation of such a marketplace.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection